A Study on Disease Resistance on Rice: Strategies and Challenges: Life Sciences-Biotechnology - Siddiqui, Nadeem; Sreeja, Nannapaneni; Supriya, Chadalavada; Sarvani, Vemuri; Bhavana, Potluri; Reddy, Siva (International Journal of Life Science and Pharma Research, 2022)
Though Rice is cultivated in huge quantities, various disease causing agents will reduce the yield leading to not only losing the economy but also a food crisis. Production of rice is constrained by fungal, bacterial and viral diseases. In the current review, we focused on various pathological symptoms in Oryza species that cause high yield losses. In this context, plant breeders are attempting progressive research activity to achieve more yield and disease-resistant varieties that balance the world’s rice demand and increase the farmers' income. Rice was recognized as a genetic model for research in genetics and molecular biology, for understanding growth, development, tolerance to stress and disease resistance because of its small genome. The present review focuses on the various causative agents of diminishing rice yield along with the strategies to eradicate the pathogen and thereby increasing the yield. Recent research advances at genetic level have paved a way for novel approach to understand the significance between the pheno-genotypic variations with the crop yield of rice. Further, the review also includes the advanced methodologies at molecular level so as to save the rice cultivators from economic crisis. Disease resistant genes are identified and screened using molecular markers like SSR (simple sequence repeats), RAPD (Randomly Amplified Polymorphic DNA), and RFLP (restriction fragment length polymorphisms) analysis. There exist few reports in the literature about rice cultivation, but to the best of our knowledge in a single review both cause and remedy were not discussed in detail. In this context, our review provides an insight into the aspects attributing the crop loss followed by suggesting the suitable alternative method for enhancing crop yield.